Buzzer Dan Elektabilitas Prabowo Gibran - Mafulah, Nita; Zulaikha, Zulaikha; Maella, Nur’annafi Farni Syam (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this research is to find out and analyze the phenomenon of political communication carried out by Buzzer on Tiktok social media to increase or decrease the electability of the Prabowo-Gibran Candidate Candidates during the 2024 Election (General Election). using qualitative methods through Emprit Drone Application Analysis. This research was carried out in the period before the first debate, Tuesday, December 12 2024 to Wednesday April 22 2024. The focus on researching the form of Buzzer Tiktok communication was carried out for 5 months. This Drone Emprit application shows concrete data regarding Buzzer accounts and how the Tiktok Buzzer effect is able to increase Prabowo-Gibran's electability by 47%, so they are able to win the 2024 presidential election. From the research results show that the Buzzer on Tiktok has a significant role in forming public opinion on TikTok. From research in this journal, it is concluded that Prabowo-Gibran's TikTok buzzer is an individual or group of people who have a social media platform on TikTok whose aim is to promote something, for a certain motive. There are paid Buzzers and there are unpaid ones. The characteristics of the Buzzer account are: Anonymous, Using the same Hashtag because often 1 vendor is created, Persuasive, has an account with promotional and persuasive purposes.